2015
DOI: 10.1167/15.2.16
|View full text |Cite
|
Sign up to set email alerts
|

Different time scales of motion integration for anticipatory smooth pursuit and perceptual adaptation

Abstract: When repeatedly exposed to moving stimuli, the oculomotor system elicits anticipatory smooth pursuit (ASP) eye movements, even before the stimulus moves. ASP is affected oppositely to perceptual speed judgments of repetitive moving stimuli: After a sequence of fast stimuli, ASP velocity increases, whereas perceived speed decreases. These two effects--perceptual adaptation and oculomotor priming--could result from adapting a single common internal speed representation that is used for perceptual comparisons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 48 publications
7
19
0
Order By: Relevance
“…In contrast, we have not addressed the question of whether and how statistical learning affects visual motion perception throughout our model-generated volatile sequences. In an empirical context similar to ours, Maus et al [10] have recently shown that perceptual adaptation for speed estimation occurs concurrently to priming-based anticipatory pursuit throughout a sequence of motion tracking trials with randomly varying speed. They actually found a robust repulsive adaptation effect, with perceptual judgements biased in favor of faster percepts after seeing stimuli that were slower and vice-versa.…”
Section: Measuring Adaptation To Volatile Environmentssupporting
confidence: 52%
See 3 more Smart Citations
“…In contrast, we have not addressed the question of whether and how statistical learning affects visual motion perception throughout our model-generated volatile sequences. In an empirical context similar to ours, Maus et al [10] have recently shown that perceptual adaptation for speed estimation occurs concurrently to priming-based anticipatory pursuit throughout a sequence of motion tracking trials with randomly varying speed. They actually found a robust repulsive adaptation effect, with perceptual judgements biased in favor of faster percepts after seeing stimuli that were slower and vice-versa.…”
Section: Measuring Adaptation To Volatile Environmentssupporting
confidence: 52%
“…Note that both these history lengths can be considered short in comparison to the several hundreds of trials that are commonly used in psychophysics and sensorimotor adaptation studies and that, similar to the present study, the inferred characteristic times are even shorter for the buildup of anticipatory eye movements. However, it is also important to note that in the study by Maus et al [10], the generative model underlying the random sequence of motion trials was different and much simpler than in the present study: In particular the role of environmental volatility was not directly addressed there. This makes a direct comparison between their results and ours difficult beyond a qualitative level.…”
Section: Measuring Adaptation To Volatile Environmentsmentioning
confidence: 55%
See 2 more Smart Citations
“…As shown in this sample screenshot, this was performed by moving a mouse cursor (black triangle) on a continuous rating scale between "Left", to "Unsure" and finally "Right". specific regularities in the properties of visual motion, such as speed, timing or direction [10,44,46]. Second, it is a robust phenomenon, which has been observed on a large population of human participants and even in non-human primates (for a recent review see [47]).…”
Section: Fig 1 Smooth Pursuit Eye Movements and Explicit Direction Pmentioning
confidence: 99%